Estado actual del mejoramiento del arroz mediante la utilización de especies silvestres de arroz en CIAT - Martínez Racines, César Pompilio; Tohme, Joseph M.; López Gerena, J.; Borrero Correa, Jaime C.; McCouch, Susan R.; Roca, W.; Chatel, M; Guimarães, Elcio Perpétuo (1998)
Current status of rice improvement through use of wild rice species at CIAT. This paper discusses the use of wild rice species to obtain an improved germplasm with a higher yield potential and a wider genetic base. Three wild species (O. rufipogon, O. glaberrima and O. barthii), and 12 improved varieties (recurrent parents) were selected to develop populations into which genes that control valuable agronomic cahracteristics are selectively transferred by the use of molecular markers. The 36 resulting populations from specific backcross schemes are now in different developmental phases, and underwent negative phenotypic selection against undesirable agronomic traits contributed by the wild parents. Between 220 and 300 BC2F2 families from specific crosses in replicated yield trials in severallocations in Colombia were evaluated. Transgressivesegregation for yield (kg/ha) was detected in the BG90-2*3/0 rufipogon population, and several families yielded between 5 and 15% more than the BG-90-2; transgressive segregation for resistance to the white leaf virus was detected in the O. llanos 5*3/0 rufipogon population. Preliminary data sugests that introgression of certain genes from O. rufipogon may contribute to yield increase in improved rice varieties.